THE INFLUENCE OF PROACTIVE PERSONALITY AND PERCEIVED ORGANIZATIONAL SUPPORT ON INNOVATIVE WORK BEHAVIOR THROUGH CREATIVE SELF-EFFICACY: A STUDY AT BANK BTN KC SEMARANG - Debby Sepridha Ametika; Suharnomo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze how much influence proactive personality and perceived organizational support have on innovative work behavior through creative self-efficacy in BTN Bank KC Semarang Office Employees. The data used in this study are primary data derived from the distribution of research questionnaires and samples in the study of 122 respondents. In the study using probability sampling is a technique where each element of the population has a chance or can be selected. The sampling technique used in the study was simple random sampling. This study uses the Structural Equation Modeling (SEM) analysis technique with the AMOS 24.0 analysis tool. The findings show that proactive personality has a positive and significant on creative self-efficacy, perceived organizational support has a direct effect on creative self-efficacy. In proactive personality has a positive and significant on innovative work behavior, perceived organization support has a positive and significant on innovative work behavior. proactive personality and perceived organization support have an effect on innovative work behavior through creative self-efficacy.